Eotaxin levels in patients with primary dysmenorrhea - Gul, Evrim; Kavak, Ebru Celik (Dove Medical Press Ltd, 2018)
Purpose: Primary dysmenorrhea (PD) is a common cause of pelvic pain that can cause limitations in daily activities. Treatment options sometimes result in failure, suggesting that different mechanisms may be effective in etiopathogenesis. Eosinophils are cells that are present in endometrium only in the perimenstrual period. The aim of this study was to evaluate the levels of eotaxin, a potent eosinophilic chemoattractant, in patients with PD. Patients and methods: Thirty patients with PD and thirty healthy women were included in the study. Venous blood sample of 10 mL was collected from each participant. Blood samples were taken in the first 2 days of the menstrual cycle at any period of the day. Serum eotaxin levels were determined by enzyme-linked immunofluorescence assay. Results: There were no statistically significant differences between the demographic properties of groups in terms of age and body mass index. Eotaxin levels were significantly different in patients with PD than the control subjects (p=0.012). Conclusion: Detection of different levels of eotaxin in patients with PD may be a new and important step in determining the factors contributing to the pathogenesis of dysmenorrhea.
Keywords: primary dysmenorrhea; eotaxin; eosinophil; ELISA; etiopathogenesis